2020
DOI: 10.4062/biomolther.2019.200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Methods for Testing Botulinum Toxin: Current Status and Future Perspectives

Abstract: Clostridium botulinum is an anaerobic, gram-positive, sporeforming, rod-shaped bacterium that produces neurotoxic proteins called botulinum toxins (Nigam and Nigam, 2010). Foodborne poisoning cases of botulinum toxins were first observed in eighteenth-century Europe, and the condition was termed 'sausage poisoning' or botulism as 'Botulus' means sausage in Latin (Kerner, 1817). Depending on the type of illness caused by botulinum toxins, C. botulinum strains are divided into four different groups. Bacterial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…In addition, this in vivo assay might take up to 24–96 h, and it might interfere with non-related BoNT toxicity of sera from autoimmune neuropathies. Alternative in vitro methods of BoNT detection are based on immunological detection such as ELISA or other immunoassays, as well as on the BoNT enzymatic activity towards their specific SNARE protein substrates (SNAP25, VAMP, syntaxin) ( Table 9 ) [ 42 , 161 , 162 , 163 , 164 ]. The sensitivity of the in vitro methods that have been developed with spiked or clinical human sera, is similar or lower than that of the mouse bioassay.…”
Section: Alternative Methods Of Bont Detection In Serummentioning
confidence: 99%
“…In addition, this in vivo assay might take up to 24–96 h, and it might interfere with non-related BoNT toxicity of sera from autoimmune neuropathies. Alternative in vitro methods of BoNT detection are based on immunological detection such as ELISA or other immunoassays, as well as on the BoNT enzymatic activity towards their specific SNARE protein substrates (SNAP25, VAMP, syntaxin) ( Table 9 ) [ 42 , 161 , 162 , 163 , 164 ]. The sensitivity of the in vitro methods that have been developed with spiked or clinical human sera, is similar or lower than that of the mouse bioassay.…”
Section: Alternative Methods Of Bont Detection In Serummentioning
confidence: 99%
“…This assay therefore presents the advantages of being able to detect biologically active toxins independently of their serotypes and to express the potency of BoNTs defined in lethal dose—LD50 Units (which corresponds to the quantity of toxin necessary to kill 50% of injected mice). The MBA also offers a high level of sensitivity, with limits of detection as low as 5–10 pg/mL [ 88 , 89 , 90 ].…”
Section: Bont Detection Assaysmentioning
confidence: 99%
“…The use of iPSCs of human origin should increase species-specific relevance and offer high sensitivity together with the possibility to compare BoNT serotypes [ 90 ]. Robust and well-characterized protocols to differentiate hPSCs into neurons are constantly in development.…”
Section: Emerging Cell-based Assays Using Human Ipscs Derivativesmentioning
confidence: 99%
“…It is reported by the CDC that ~15% of the 145 botulism cases reported in 2011 were foodborne (CDC Report 2011). Due to the highly toxic nature and frequent occurrence of these neurotoxins, it is critical to screen and detect C. botulinum rapidly in order to prevent further outbreak of the pathogens [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Moreover, it is constantly demonstrated that it is imperative to have the kits available for quick, initial high-throughput screening of the presence of the pathogens and for further control of the potential pandemic of any infectious diseases, such as the well-known SARS outbreak in 2003 and the current COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%